2021
DOI: 10.3390/jof7110966
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Fungal Keratitis in the United Kingdom 2011–2020: A 10-Year Study

Abstract: Fungal keratitis (FK) is a serious ocular infection that often poses significant diagnostic and therapeutic dilemmas. This study aimed to examine the causes, clinical characteristics, outcomes, and prognostic factors of FK in the UK. All culture-positive and culture-negative presumed FK (with complete data) that presented to Queen’s Medical Centre, Nottingham, and the Queen Victoria Hospital, East Grinstead, between 2011 and 2020 were included. We included 117 patients (n = 117 eyes) with FK in this study. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 63 publications
(107 reference statements)
2
37
0
Order By: Relevance
“…However, in a real-world setting, diagnosis of infectious keratitis often poses significant diagnostic and therapeutic dilemmas, often due to indistinguishable clinical features shared among different causative organisms and polymicrobial infection [ 19 ]. Feathery infiltration and retrocorneal endothelial plaques are commonly associated with fungal keratitis [ 20 , 21 ]; however, in some cases, viral keratitis will mimic fugal keratitis and present with similar characteristics, which will be misdiagnosed easily and delay the treatment [ 18 , 22 ]. The inherent limitations of conventional microbiological testing such as variably low culture positivity rate and a long turnaround time are a recurrent theme in literature [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a real-world setting, diagnosis of infectious keratitis often poses significant diagnostic and therapeutic dilemmas, often due to indistinguishable clinical features shared among different causative organisms and polymicrobial infection [ 19 ]. Feathery infiltration and retrocorneal endothelial plaques are commonly associated with fungal keratitis [ 20 , 21 ]; however, in some cases, viral keratitis will mimic fugal keratitis and present with similar characteristics, which will be misdiagnosed easily and delay the treatment [ 18 , 22 ]. The inherent limitations of conventional microbiological testing such as variably low culture positivity rate and a long turnaround time are a recurrent theme in literature [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the initial severity of the ulcer and presenting visual acuity serve as important prognostic factors for IK (Khoo et al, 2020 ; Ting et al, 2021a , c ). Therefore understanding the risk factors via big data research allows for effective implantation of various preventative strategies in reducing the incidence of IK.…”
Section: Big Data In Corneal Diseasesmentioning
confidence: 99%
“…The sooner the initial empirical treatment is consolidated to target the pathology, the more likely there will be a better outcome. Ting et al [ 13 ] summarized 10-years of results in fungal keratitis (FK) patients in the UK: 81.2% of 117 subjects included required hospitalization for intensive treatment with a mean hospitalization of 18.9 ± 16.3 days. Additionally, nearly 25% of the total cohort reported a final corrected distance visual acuity of perception of light or worse with up to 9.4% of cases where eye enucleation was required.…”
Section: Introductionmentioning
confidence: 99%